Eksplorasi Gaya Interior Maritim sebagai Representasi Budaya Pesisir pada Maritime Food Society di Pelindo Tower Jakarta Utara - Fiqih Ahmad Dzaky; Erina Wiyono (Journal of Innovative and Creativity, 2025)
Interior design serves not only as an aesthetic component but also as a medium for representing culture and local identity. This study explores how maritime interior style can be used to represent coastal culture in North Jakarta through a case study of the Maritime Food Society restaurant at Pelindo Tower. Using a visual semiotics approach, the research examines interior elements such as color, material, visual symbols, and spatial layout as a system of signs that convey the cultural values of coastal communities. The study employs a thematic literature review method, drawing upon theories of emotional design (Norman, 2004) and design-driven innovation (Rampino, 2011), as well as visual analysis of interior documentation. Findings indicate that elements such as fishing nets, aquariums, anchor symbols, and the use of natural materials create spatial narratives that reflect maritime life. However, challenges arise in maintaining authenticity and avoiding the commodification of culture when these elements are used decoratively without narrative context. Therefore, an interpretive design approach is needed—one that integrates cultural symbolism with reflective user experience. This research highlights the significance of interior design as a cultural communication space that unifies aesthetics, function, and local identity in a contextual and meaningful way.